Increasing the Possibility Economy of Bali City Through the Development of Small Industry - Valiant Michelle; Ericko Ericko; Ervi Scorpianti; Jessy Jessy (Eduvest - Journal of Universal Studies, 2021)
GRDP plays an important role in the economic growth of a region. The high rate of GRDP can encourage regional growth and development. The growth of cities and their surrounding areas is closely linked to economic change, especially as it can create opportunities for more productive jobs that can contribute to attracting foreign trade and investment. The industrial sector is one of the largest contributors to GRDP in Bali after the trade sector and the banking sector and other financial institutions. The industrial sector is the largest employer of labor, with a positive growth rate every year, especially in 2019. This research used econometric model approach to co-integration and dynamic model approaches ECM (Error Correction Model) for methods of analysis.  The results of multiple linear regression to estimate ECM shows that domestic investment (PMDN) and foreign investment (PMA) have influences toward GDRP in industry. In the short-term and long-term shows that domestic and foreign variable have positive and significant effect on the value of GDRP along with all industry including small industry. The aim of this study is to explore new things, new ideas, hypotheses and analyze the importance of the role and development of small industries in increasing the GRDP of the City of Bali.